2019
DOI: 10.1096/fj.201901818rr
|View full text |Cite
|
Sign up to set email alerts
|

Lineage specification and pluripotency revealed by transcriptome analysis from oocyte to blastocyst in pig

Abstract: The inner cell mass (ICM) in blastocyst is the origin of all somatic and germ cells in mammals and pluripotent stem cells (PSCs) in vitro. As the conserved principles between pig and human, here we performed comprehensive single‐cell RNA‐seq for porcine early embryos from oocyte to early blastocyst (EB). We show the specification of the ICM and trophectoderm in morula and the molecular signature of the precursors. We demonstrate the existence of naïve pluripotency signature in morula and ICM of EB, and the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 43 publications
2
71
0
1
Order By: Relevance
“…Publicly available datasets were analyzed in this study ( Kim et al, 2018 ; Kong et al, 2020 ). These data can be found in the Gene Expression Omnibus database 1 under accession number GSE139512 and GSE108570 .…”
Section: Methodsmentioning
confidence: 99%
“…Publicly available datasets were analyzed in this study ( Kim et al, 2018 ; Kong et al, 2020 ). These data can be found in the Gene Expression Omnibus database 1 under accession number GSE139512 and GSE108570 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies of porcine embryo had verified a number of common markers and discovered pig-specific lineage markers [ 20 , 21 , 22 ]. We have identified the trends of the marker gene expression in the porcine embryos ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Using single cell qPCR, stage- and lineage-specific genes were identified, and ICM/TE cells were sorted according to the patterns of the marker gene expression [ 20 ]. Cells were categorized into lineage groups based on the single cell RNA-seq, and it has been demonstrated that certain conventional lineage markers (e.g., CDX2 and TEAD4 ) do not correspond to markers detected in porcine embryos [ 21 , 22 ]. A number of studies have been investigating in vivo embryos; however, detailed information about in vitro fertilized (IVF) porcine embryos remains unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…NANOG knock-in positive PC-iPS cells were positive to AP staining (Additional file 3: Figure S2C), the method of AP staining is reference for our publication data [14]. Clustering analysis showed that knock-in positive PC-iPS cells could be clustered with pig EPS cells [12], but were separate from trophoblast cell (TE), inner cell mass (ICM), and early blastocyst (SB) [43] ( Fig. 2A) (further detail provided in Additional file 4: Table S2); knock-in positive PC-iPS were expressed OCT4 and SOX2 pluripotent markers (Fig.…”
Section: Verification and Transcriptome Analysis Of Nanog Tdtomato Knmentioning
confidence: 95%
“…KEGG pathway analyses were performed using ClusterProfiler [42]. Reanalyzed previously published data are available under the accession codes GSE139512 [43] for pig preimplantation embryos and E-MTAB-7253 [12] for pig EPS cells.…”
Section: Rna Sequencing and Transcriptome Analysismentioning
confidence: 99%